Stability analysis of surrounding rocks of deeply-buried underground chambers based on the improved block theory and simulation using unwedge computer program - Fugui Tao; Anyi Lan; Lei Han; Xudan Sun; Zhixi Liu (Electronic Journal of Structural Engineering)
To tackle the challenges of extensive drawing workloads and limited precision inherent in the application of block theory, this paper presents an optimization of block theory based on an improved vector method. Additionally, the Unwedge computer program is employed to conduct visual simulations of block theory applications, thereby enhancing the ease of utilizing block theory. To validate the accuracy of our research findings, we conducted a case study on the stability of surrounding rock in the deeply buried underground caverns with complex geological structures at the Jinping-II Hydropower Station. The research results reveal that the refined vector method can swiftly identify the stability of surrounding rock in various study areas, offering a valuable reference for the practical excavation of underground caverns. In the engineering case, safety concerns arise in key block zones with safety factors below 1.5, necessitating the implementation of appropriate safety measures during excavation. Furthermore, some key blocks exhibit a safety factor of zero and are positioned at the top of the cavern. In theory, these key blocks could have a certain impact on the stability of the surrounding rock of the cavern. However, given their minute volume and weight, they can be deemed stable. By comparing the refined block theory and computer program calculation results with the actual construction and excavation process of the underground cavern, we found that they are largely consistent. This underscores that the improved method proposed in this paper can provide theoretical support and a feasible basis for the excavation of deeply buried underground caverns.